Enig Verschil nieuwsbrief. - Enig Verschil (EV) (Antwerpen : EV, 1994)
Fonds Suzan Daniel (FSD)
Periodiciteit : [tweemaandelijks?]
Redactie : PB 22, 2060 Antwerpen 9 ; vanaf (1998) sep : PB 144, 2000 Antwerpen 1
Voortgezet als 'Versch Geperst' 08(2001) 3
Nederlands
Periodiek